Clinicopathological and Molecular Analysis of 45 Cases of Pure Mucinous Breast Cancer - Yim, Hyun Ee; Kim, Jang-Hee; Ahn, Mi Sun; Jung, Yongsik; Roh, Jin; Park, So Hyun; Kim, Tae-Gyu; Choi, Jin-Hyuk; Kang, Seok Yun (Frontiers in Oncology, 2021)
Pure mucinous breast carcinoma (PMBC) is characterized by clusters of tumor cells floating in abundant extracellular mucin and can be classified into paucicellular (Type A) and hypercellular (Type B) subtypes. However, the clinicopathological and genomic differences between these two subtypes have not been well characterized. We retrospectively investigated the clinicopathologic features of 45 cases of surgically removed PMBC (31 Type A and 14 Type B). We also performed whole-exome sequencing (WES) in 8 cases of PMBC. We found that Type B PMBC occurs at an older age and shows more aggressive clinical behavior than Type A. WES analysis revealed that HYDIN was the most frequently mutated gene in both types of PMBC. Although Type B PMBC showed a tendency toward more frequent genetic alterations, there were no statistically significant differences between the two subtypes in single nucleotide variants or insertions or deletions of bases associated with moderate or high effects. Our results provide additional evidence that PMBCs are clinicopathologically and genetically heterogeneous and lack pathognomonic genetic alterations. Further, Type B PMBC is more frequently associated with lymph node metastasis than Type A.